2021
DOI: 10.1021/acs.jpcc.0c09117
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Computational Screening of Metal–Organic Frameworks for the Separation of Methane from Ethane and Propane

Abstract: Efficient separation of mixtures of light hydrocarbons is an industrially demanding but challenging process. In this study, we present a high-throughput computational screening of ∼12,000 experimentally realizable metal–organic framework (MOF) structures in order to identify the best candidate that can separate methane from ethane and propane at ambient conditions. We calculated several performance metricsadsorption selectivity, working capacity, and regenerability to assess the performance of the MOFs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…203,159,204 This method involves the simulation of adsorption properties for the desired target gases, with the aim to single out those materials that are predicted to provide the best separation performance, evaluated using metrics such as selectivity, working capacity, energy penalty or composite metrics derived therefrom. The focus of these studies used to be primarily on CO2 separations, 102,131,[205][206][207][208][209][210][211][212][213][214][215][216][217][218][219] but recent years have seen a broadening in scope, to cover also hydrocarbons separation, [220][221][222] acetylene purification 91 and Xe/Kr separation. [223][224][225] These computation-based approaches provide a large amount of information that can, in principle, be very valuable to chemists at the sorbent development stage, allowing to make better decisions about the type of material to target for a certain gas separation.…”
Section: Role Of Computational Studiesmentioning
confidence: 99%
“…203,159,204 This method involves the simulation of adsorption properties for the desired target gases, with the aim to single out those materials that are predicted to provide the best separation performance, evaluated using metrics such as selectivity, working capacity, energy penalty or composite metrics derived therefrom. The focus of these studies used to be primarily on CO2 separations, 102,131,[205][206][207][208][209][210][211][212][213][214][215][216][217][218][219] but recent years have seen a broadening in scope, to cover also hydrocarbons separation, [220][221][222] acetylene purification 91 and Xe/Kr separation. [223][224][225] These computation-based approaches provide a large amount of information that can, in principle, be very valuable to chemists at the sorbent development stage, allowing to make better decisions about the type of material to target for a certain gas separation.…”
Section: Role Of Computational Studiesmentioning
confidence: 99%
“…On the basis of the CoRE MOF 2019, Solanki and Borah presented a high-throughput screening based on adsorption selectivity, working capacity, regenerability, and adsorbent performance score to identify candidate materials for propane/propene separations, reporting BOLZIN (NU-1100) as the best performing MOF. Ponraj and Borah performed similar high-throughput screening for the separation of methane from ethane and propane and found that the MOFs AZIVAI and BEWCUD performed well.…”
Section: Introductionmentioning
confidence: 92%
“…Borah and Ponraj screened about 12 000 MOFs for C 2 H 6 /CH 4 separation and highlighted that MOFs with the Zr 4+ cation are promising candidates for purification of CH 4 . 25 MOFs have also been investigated for membrane-based CH 4 /C 2 H 6 and CH 4 /H 2 separations, 26 , 27 and all of these works have highlighted the high potential of MOFs for CH 4 purification.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al used molecular simulations to examine CH 4 /N 2 mixture separation potentials of 5109 MOFs and revealed that MOFs with pore-limiting diameters (PLDs) in the range of 3.8–4.7 Å achieve high selectivities. Borah and Ponraj screened about 12 000 MOFs for C 2 H 6 /CH 4 separation and highlighted that MOFs with the Zr 4+ cation are promising candidates for purification of CH 4 . MOFs have also been investigated for membrane-based CH 4 /C 2 H 6 and CH 4 /H 2 separations, , and all of these works have highlighted the high potential of MOFs for CH 4 purification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation